Deprotonation of group 14 metal amide complexes bearing ditopic carbanionic n-heterocyclic carbene ligands. Constitutional isomerism and dynamic behavior - Waters, J; Tucker, L; Goicoechea, J (American Chemical Society, 2017)
The reactivity of the lithiated N-heterocyclic carbene [:C[N(2,6- i Pr 2 C 6 H 3 )] 2 (CH)CLi] ∞ with two-coordinate homoleptic group 14 amides E[N(SiMe 3 ) 2 ] 2 (E = Sn, Pb) is described. Solutions of these mixtures readily result in the formal loss of 1 equiv of bis(trimethylsilyl)amine, HN(SiMe 3 ) 2 , to afford novel metallacycles. Reactions involving Sn[N(SiMe 3 ) 2 ] 2 initially give rise to the anionic complex [{:C[N(2,6- i Pr 2 C 6 H 3 )] 2 C(CH)}Sn{N(SiMe 3 ) 2 } 2 ] - (1), which eventually affords the novel distannane [{(THF) 2 Li:C[N(2,6- i Pr 2 C 6 H 3 )] 2 (CH)C}Sn{μ-κ 1 :κ 1 -N(SiMe 3 )(SiMe 2 CH 2 )}Sn{C(CH)[N(2,6- i Pr 2 C 6 H 3 )] 2 C:}{N(SiMe 3 ) 2 }] (2), in which one of the trimethylsilyl substituents has been deprotonated and bridges the Sn-Sn bond, affording a five-membered metallacycle. By contrast, reactions involving Pb[N(SiMe 3 ) 2 ] 2 give rise to a species that may be considered a constitutional isomer of 2, [{(THF) 2 Li:C[N(2,6- i Pr 2 C 6 H 3 )] 2 (CH)C}Pb{N(SiMe 3 ) 2 }{C(CH)[N(2,6- i Pr 2 C 6 H 3 )] 2 C:}Pb{κ 2 -N(SiMe 3 )(SiMe 2 CH 2 )}] (3), featuring a base-stabilized plumbylene species. The dynamic behavior of 3 in solution suggests stereochemical inversion at the plumbylene moiety, Pb{κ 2 -N(SiMe 3 )(SiMe 2 CH 2 )}, a process which can be retarded at low temperatures, allowing for the observation of the two inequivalent proton environments of the methylene bridge. This process is believed to involve rapid intermolecular transfer of the plumbylene fragment between the ditopic carbanionic carbene ligands of the plumbyl core.